Implementasi Penyesuaian Obat Diabetes pada Saat Puasa Ramadan dan Pengaruhnya Terhadap Nilai HbA1c - Rahmi Safyanty; Retnosari Andrajati; Sudibyo Supardi; Ratu Ayu Dewi Sartika (Jurnal Sains Farmasi & Klinis, 2020)
This study aimed to evaluate the effect of diabetes medication adjustment during Ramadan fasting according to the recommendation of International Diabetes Federation-Diabetes and Ramadan International Alliance (IDF-DAR) to HbA1c values in type-2 diabetes mellitus patients. The study was conducted at a hospital in Jakarta, Indonesia with a cross-sectional study design involving 80 ambulatory patients with type-2 DM who fasted during Ramadan in 2016. About 60% of patients used oral antidiabetes drug (OAD), mostly the combination of biguanide + sulfonylurea drugs (27.5%). The adjustments were made in which 56.2% was in accordance with IDF-DAR recommendations. The study showed that the HbA1c values decreased insignificantly (p = 0.082) from 8.75 ± 1.90 to 8.63 ± 1.82 after the adjustment. The appropriate drug adjustment based on IDF-DAR had a significant effect on the HbA1c value of DM patient with p-value 0.030 (p < 0.05).The discrepancy of drug use based on IDF-DAR 3.222 times greater caused uncontrolled HbA1c. The most influential variable to HbA1c value was drug type with p-value 0.006 (p < 0.05). Improper adjustment of Insulin or combination insulin-OAD caused HbA1c value 5 times greater to be uncontrolled than OAD.